Protocol for a theory-based, mixed methods evaluation of Cynnau|Ignite: an active learning programme to foster positive research culture through leadership development at Cardiff University - Charlotte Hennah; Maleeha Rizwan; Nicola Edwards; Hayley Beckett; Michele Convery; Heidi Dawson; Jonathan Morris; Mair Rigby; James Vilares; Karin Wahl-Jorgensen; Rebecca Williams; Sofia Gameiro (PLoS ONE, 2025)
A recent UKRI call for training programmes to improve research culture at Higher Education Institutions led Cardiff University to design Cynnau|Ignite. This active learning programme intends to foster positive research culture practices through empowering staff towards leadership on this agenda, and by embedding learners in environments where these practices are highly valued. Cynnau|Ignite will be implemented within Cardiff University as three tailored programmes, dependant on job roles: Teaching and Research (64 learners), Research-Only (32 learners), and Professional Services, Technicians and Specialists (32 learners). This protocol details a theory-based, mixed methods evaluation of Cynnau|Ignite’s effectiveness, acceptability, and feasibility as a tool to improve research culture practices and perceptions within Cardiff University. This knowledge will help inform future iterations of Cynnau|Ignite and similar initiatives, while advancing methods for the evaluation of positive research culture practices, and has potential to inform choices regarding funding and evaluation of research culture initiatives at other Higher Education Institutions. Here, we outline the Cynnau|Ignite Theory of Change used to inform our primary outcomes and describe our plan to evaluate the programme’s effectiveness by measuring learners’ self-reported positive research culture practices (intentions and behaviours) before and after taking part in Cynnau|Ignite, in comparison to a control group of staff who were not involved in the programme. Additionally, data monitoring, sessions observation, and semi-structured interviews will be conducted to establish programme acceptability and feasibility for stakeholders including learners, the delivery team, and university management. We hypothesise Cynnau|Ignite will be largely acceptable and effective in boosting learners’ positive research culture intentions compared to a control group, but believe behavioural implementation may be adversely affected by common barriers such as insufficient time and resources. Overall, we expect Cynnau|Ignite to improve short-term positive research culture practices and perceptions at Cardiff University, but its potential long-term impact is unclear. Study registration Number: ISRCTN15575518